P0496THE IMPORTANCE OF COMPLEMENT LEVELS AND CLINICAL CHARACTERISTICS OF PRIMARY MEMBRANOPROLIFERATIVE GLOMERULONEPHRITIS IN TURKEY. (6th June 2020) - Tatar, Erhan; Oygar, Deren; Seyahi, Nurhan; Eren, Necmi; Cantürk, Yağmur; Güngör, Özkan; Derici, Ülver; Sipahioğlu, Murat; Yıldız, Abdülmecit; Karadağ, Serhat; Sumnu, Abdullah; Odabas, Ali Riza; et al.
Abstract: Background and Aims: Membranoproliferative glomerulonephritis (MPGN) may be caused by disturbances in the complement system. Hypocomplementemia is a characteristic of MPGN. Among these patients frequency of hypocomplementemia and their relation with clinical and histopathological findings are still not clearly known. The aim of this study is to evaluate the hypocomplementemia frequency among the primary MPGN patients in Turkey and its relation with histopathological subtypes, findings and demographic characteristics. Method: The data was obtained from national multicentered (47 centers) records of primary glomerular diseases in Glomerulonephritis Study Group of the Turkish Society of Nephrology database from May 2009 to June 2019. Primary MPGN cases were evaluated and divided into 2 groups with and without hypocomplementemia. Results: In total, 193 cases were included in the study. The indications for renal biopsy were isolated nephrotic syndrome (55.4%), nephritic syndrome (21.2%), nephrotic syndrome with a nephritic component (6.2%) and asymptomatic urinary findings (17.2%). 34.2% of the cases were reported as immune complex type, another 34.2% of the cases were reported as C3 glomerulopathy. 31.6% of patients were not specified. 82 (42.4%) of the cases presented hypocomplementemia. Hypocomplementemic patients were younger (34±14 vs 41±15, p=0.002) and most frequently female (56% vs 41%, p=0.03). At same time, serum albumin and hemoglobin levels were lower and anemic patient rates were higher (p<0.001). In this group, the nephrotic syndrome rates were higher (72% vs 54%, p=0, 01). Hypocomplementemia rate in the C3 glomerulopathy was 52% (in DDD 40%, in C3GN 55% ) whereas in immune complex type 41% and in non specified type 34%. In the pathological evaluation; among the hypocomplementemic group the endocapillary proliferation and glomerular exudative differentiation rates presented significant increase. However the chronicity index were lower in the kidney biopsy (Table 1). Conclusion: This multicenter study provided important data about the epidemiology of MPGN with importance of hypocomplementemia in Turkey. Hypocomplementemia is associated with both subtypes of MPGN patern, anemia and nephrotic syndrome. At the same time, hypocomplementemia is a valuable parameter for active MPGN pattern in the histopathological evaluation. This may be important in determining the treatment.